Gondwanan survivor lineages and the high-risk biogeography of Anthropocene Southeast Asia - Kooyman, Robert M.; Ivory, Sarah J.; Benfield, Adam J.; Wilf, Peter (Journal of Systematics and Evolution, 2022)
The Southeast Asian rainforest region is extremely complex and biodiverse. Fossils have shown that paleo‐Antarctic rainforest lineages (PARLs) now extant in Asia tracked the ever‐wet conditions needed to survive and diversify through deep time. However, the threat of future climate change to the remaining rainforest and PARLs in Southeast Asia has yet to be evaluated to set conservation priorities. We first quantified the woody‐genus floristic relationships of Southeast Asian Island Groups by vetting and analyzing recent compilations of bioregional species data. We then evaluated the contributions to community assembly of woody fossil lineages and Island Group relationships to environmental gradients. To better understand climatic constraints of fossil lineage distributions and forecast distributions under projected future climate, we used exemplar living woody PARLs, including two angiosperms and two gymnosperms. Generalized linear models were used to project potential distributions under future climate pathways that assume no reduction in carbon dioxide emissions. The floristic analyses highlighted strong similarities among Island Groups in the ever‐wet forest areas of Malesia, where PARLs are often concentrated. Ordination outliers represented more seasonal locations. Species distribution models showed that potential future distributions of ancient lineages are constrained by increasing rainfall seasonality and higher seasonal temperatures, with significant differences among exemplar genera. Notably, potential distributions often mapped onto de facto inaccessible areas, where forest clearing and the ubiquitous marine dispersal barriers that characterize the region will drastically inhibit potential relocation. These realities gravely threaten paleo‐conservation values and contemporary rainforest community assembly processes in Southeast Asia.